Time course of histomorphological changes in adipose tissue upon acute lipoatrophy - Murano, Incoronata (2012)
BACKGROUND AND AIMS: Crown-like structures (CLS) are characteristic histopathology features of inflamed adipose tissues in obese mice and humans. In previous work, we suggested that these cells derived from macrophages primarily involved in the reabsorption of dead adipocytes. Here, we used a well-characterized transgenic mouse model in which the death of adipocytes in adult mice is inducible and highly synchronized. In this “FAT-ATTAC” model, apoptosis is induced through forced dimerization of a caspase-8 fusion protein. METHODS AND RESULTS: 0, 0.5, 1, 2, 3 and 10 days post induction of adipocyte cell death, we analyzed mesenteric and epididymal adipose depots by histology, immunohistochemistry and electron microscopy. Upon induction of caspase-8 dimerization, numerous adipocytes lost immunoreactivity for perilipin, a marker for live adipocytes. In the same areas, we found adipocytes with hypertrophic mitochondria and signs of organelle degeneration. Neutrophils and lymphocytes were the main inflammatory cells present in the tissue, and the macrophages were predominantly Mac-2 negative. Over the course of ablation, Mac-2 positive macrophages substituted for Mac-2 negative macrophages, followed by CLS formation. All perilipin-negative, dead adipocytes were surrounded by CLS structures. The time course of histopathology was similar in both fat pads studied, but occurred at earlier stages and was more gradual in mesenteric fat. CONCLUSION: Our data demonstrate that CLS formation results as a direct consequence of adipocyte death, and that infiltrating macrophages actively uptake remnant lipids of dead adipocytes. Upon induction of adipocyte apoptosis, inflammatory cells infiltrate adipose tissue initially consisting of neutrophils followed by macrophages that are involved in CLS formation.